Effect of novel fiber ingredients on ileal and total tract digestibility of energy and nutrients in semi‐purified diets fed to growing pigs. (1st November 2013) - Cervantes‐Pahm, Sarah K; Liu, Yanhong; Evans, Annette; Stein, Hans H
Abstract BACKGROUND Consumption of different dietary fibers may influence the digestibility of carbohydrates and other nutrients. Therefore the objectives of this experiment were to determine the effect of novel fiber ingredients on the apparent ileal digestibility (AID) and apparent total tract digestibility (ATTD) of gross energy (GE), dry matter (DM), crude protein (CP) and total dietary fiber (TDF) in pigs and to calculate the standardized digestibility of analyzed TDF in four novel fiber ingredients. RESULTS The AID of DM and GE in diets containing novel fiber ingredients was less (P < 0.05) than in a maltodextrin diet. Addition of cellulose or pullulan, but not resistant starch (RS) 60, RS 75 or soluble corn fiber 70, reduced (P < 0.05) the AID of CP. The average ileal and total tract endogenous losses of analyzed TDF were calculated at 25.25 and 42.87 g kg−1 DM intake, respectively. CONCLUSION Addition of novel fiber ingredients to a maltodextrin‐based diet had different effects on the AID of DM, CP, GE and TDF. Measurements of the standardized digestibility of analyzed TDF may be a better indicator of TDF fermentability than measurements of AID and ATTD of TDF, because some endogenous metabolites may be analyzed as TDF. © 2013 Society of Chemical Industry